LEGAL AND REGULATORY ISSUES OF ISLAMIC FINANCE IN TURKEY: A QUALITATIVE DISCUSSION - Yas, Murat (Bank Indonesia, 2023)
This study aims to explore issues related to Islamic financial regulations in Turkey through the use of semi-structured interviews. A total of 12 respondents were involved, including regulators, members of the Central Advisory Board (CAB), the Advisory Board of Islamic Financial Institutions (IFIs), and managers from IFIs in Turkey. The results highlight consistent calls for the establishment of an act for the Participation finance industry. This act is seen as a means to ensure tax neutrality, reinforce norm hierarchy, prevent the imitation of conventional financial products, and mitigate Shari’ah non-compliance risk. Additionally, our empirical findings emphasise the importance of enhancing stakeholder engagement, clarifying roles, establishing a robust organizational structure, and enhancing transparency and independence for regulatory authorities. Improved regulatory governance is crucial for enhancing regulatory outcomes. Lastly, the study underscores the need for standardised guidelines for PFIs and emphasises the significance of their voluntary implementation.